Study of Pressure Distribution on an Irregular Octagonal Plan Oval-Shape Building Using CFD - Arun Kumar; Ritu Raj (Civil Engineering Journal, 2021)
This paper aims to study the wind flow characteristics and to analyze the wind pressure distribution on the surfaces around an irregular octagonal plan shape building model. There is a central open space in plan to provide more surface area around the building for natural ventilation. Plan area of the building is 300 m2(excluding the open space) and height is 50 m. Steady state flow of wind with 5% turbulence (moderate turbulence) under atmospheric boundary layer has been taken in the study. Numerical simulation with standard k-e model using ANSYS (CFX) software has been used for the purpose. Flow characteristics has been studied in terms of flow separation, reattachment of flow, creation of wakes and vortices. The surface pressure generated around the model has been studied in terms of coefficient of pressure. The model is symmetrical about both the axes in plan. Hence, study for different wind angle of attacks from 0° to 90° @ 30° interval has been conducted. The flow characteristics and unusual or critical coefficient of pressure on surfaces of the model observed have been discussed. Doi: 10.28991/cej-2021-03091760 Full Text: PDF